An epidemiological study on pattern of thoraco-abdominal injuries sustained in fatal road traffic accidents of Bangalore: Autopsy-based study - N Bayapa Reddy; Hanumantha; Pallavi Madithati; N Nagarjuna Reddy; C Sainarasimha Reddy (Journal of Emergencies, Trauma and Shock, 2014)
Background: The statistical profile reflects a global estimate of 5.1 million deaths in 2000, which was due to injuries that accounted for 10% of deaths due to all causes. Out of this, a quarter of injury-related deaths occurred in the South-East Asian region. Road Traffic Accident (RTA) is one among the top 5 causes of morbidity and mortality in South-East Asian countries. Most common cause of blunt abdominal trauma in India is road traffic accident followed by pedestrian accidents, abdominal blows, and fall from heights. Aims: To analyze the epidemiology and pattern of fatal thoraco-abdominal injuries in road traffic accidents. Materials and Methods: An autopsy-based cross-sectional study conducted. A purposive sampling technique was applied to select the study sample of 100 post-mortems of road traffic accident between November 2008 and May 2010 subjected to medico-legal autopsy at the department of Forensic Medicine, KIMS Hospital Bangalore. Results: The majority of the victims were aged 21 to 40 years, 50 (50.0%), most of the victims were male 92 (92.0%); and male/female ratio was 11.5:1. Commonest offending agents in heavy motor vehicles were 54 (54.0%). Bony cage sustained injuries were observed in 71; out of this, fractures of ribs were observed in 45 (63.3%) victims, clavicle in 14 (19.7%), sternum was 6 (8.4%), and vertebrae 6 (8.4%) of fatal road traffic accidents. Internal thoracic injuries were observed in 26 cases. Among internal thoracic injuries, lungs were the most commonly involved organ 24 (92.3%) followed by the heart 2 (7.6%). Lung sustained more lacerations 19 (79.1%) than contusions 5 (20.8%). Internal abdominal injuries were observed in 49 cases. In road traffic accidents, the most commonly injured abdominal organs were solid organs such as liver 16 (32.6%) followed by spleen 9 (18.3%). Conclusions: Majority of the times in road traffic accidents, young and productive males were injured or lost their life. This study may help the planners to take safety measures, to implement strict traffic rules, to risk stratification in the susceptible population to educate the people, and the study of nature of offending agent in RTA can help the authorities to plan better availability of health care on roads.